2008
DOI: 10.1007/s10661-008-0583-0
|View full text |Cite
|
Sign up to set email alerts
|

Ambient elemental, reactive gaseous, and particle-bound mercury concentrations in New Jersey, U.S.: measurements and associations with wind direction

Abstract: Two and a half years of data of ambient concentrations of elemental mercury (Hg(0)), reactive gaseous mercury (RGM), and particle-bound mercury (Hg(p)) were collected at measurement sites at Elizabeth, New Jersey and New Brunswick, New Jersey with Tekran sampling units. The data were processed, summarized, and analyzed from a variety of perspectives. Data quality control and quality assurance procedures are described. Wind direction and wind speed data for each of the sites were also collected. Significant tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Effects of wind on ambient levels of speciated mercury had been demonstrated to mainly facilitate transport from upwind sources by examining the wind rose of mercury concentrations and backward trajectories of mercury rich air masses (e.g., Poissant et al, 2005;Gariel et al, 2005;Sigler et al, 2009a;Aucott et al, 2009) and to enhance mercury evasion (Gårdfeldt et al, 2003;Sigler et al, 2009b). Our study confirmed such effects of wind speed and direction on mercury.…”
Section: Windsupporting
confidence: 82%
See 1 more Smart Citation
“…Effects of wind on ambient levels of speciated mercury had been demonstrated to mainly facilitate transport from upwind sources by examining the wind rose of mercury concentrations and backward trajectories of mercury rich air masses (e.g., Poissant et al, 2005;Gariel et al, 2005;Sigler et al, 2009a;Aucott et al, 2009) and to enhance mercury evasion (Gårdfeldt et al, 2003;Sigler et al, 2009b). Our study confirmed such effects of wind speed and direction on mercury.…”
Section: Windsupporting
confidence: 82%
“…Some studies often found association between high concentrations of mercury and wind direction which points to upwind source regions (e.g., Gabriel et al, 2005;Poissant et al, 2005;Aucott et al, 2009;Sigler et al, 2009a;Baya and van Heyst, 2010), while others detected no correlation (Castillo et al, 2011). In addition, our previous study found a relationship between wind speed and possible oceanic evasion (Sigler et al, 2009b).…”
Section: H Mao Et Al: Speciated Mercury At Marine Coastal and Inlmentioning
confidence: 64%
“…Ambient TGM concentrations measured 4.3 m above the Secaucus High School Marsh ranged from 1.4 to 5.1 ng m −3 (Table 2). The average summertime concentration of TGM at the Secaucus site (2.5 ng m −3 ) was similar to that observed in Bayonne, New Jersey (2.2 ng m −3 ) 18 km to the south [ Goodrow et al , 2005] and Elizabeth, New Jersey (2.3 ng m −3 ) 23 km to the south–southwest [ Aucott et al , 2009]. Ambient TGM concentrations measured 3.2 m above the marsh surface at the Great Bay estuary site ranged from 2.3 to 3.4 ng m −3 (Table 3).…”
Section: Resultssupporting
confidence: 55%
“…Atmospheric mercury exists primarily (up to 99%) in the gaseous elemental (Hg 0 ) form, [ Zillioux et al , 1993; Lin and Pehkonen , 1999; Aucott et al , 2009], but reactive gaseous mercury may be present at greater than 1% under certain conditions [ Sheu and Mason , 2001]. Although we did not measure gaseous mercury speciation in this study, elemental mercury represented more than 99.4% of the total gaseous mercury measured continuously over a two and a half year period (2004–2006) at an urban/industrial site in Elizabeth, New Jersey [ Aucott et al , 2009] 23 km to the south–southwest of the Secaucus site. Total gaseous mercury concentrations are therefore assumed to be dominated by elemental mercury and the vertical fluxes estimated using are assumed to be representative of gaseous elemental mercury.…”
Section: Methodsmentioning
confidence: 99%
“…Wind data have been used to trace back the origin of high mercury concentrations. Some studies often found association between high concentrations of mercury and wind direction which points to upwind source regions (e.g., Gabriel et al, 2005;Poissant et al, 2005;Aucott et al, 2009;Sigler et al, 2009a;Baya and van Heyst, 2010), while others detected no correlation (Castillo et al, 2011). In addition, our previous study found a relationship between wind speed and possible oceanic evasion (Sigler et al, 2009b).…”
Section: Introductionmentioning
confidence: 64%